1980
DOI: 10.1093/geronj/35.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Processing Consequences of Perceptual Grouping in Selective Attention

Abstract: Two experiments examined adult age differences in the effects of perceptual grouping on attentional performance. In a search task, 48 young, middle-aged, and elderly subjects sorted cards based on the orientation of a target figure. The interfering effects of irrelevant information which did or did not contrast with the target in orientation were examined. The position of targets varied from one card to the next. Elderly, but not young or middle-aged subjects were slowed by the presence of contrasting irreleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 0 publications
1
40
0
Order By: Relevance
“…Wright and Elias (1979) found significantly smaller response compatibility effects for old than for young subjects. However, Farkas and Hoyer (1980) found that old subjects' performance was more severely disrupted than young subjects' when they responded to a target in the presence of similarly shaped distractors (see also R. Shaw, 1991). Cerella (1985a) hypothesized that these discrepant findings might be the result of uncontrolled age-related acuity differences rather than attentional factors.…”
Section: Stopping Taskmentioning
confidence: 99%
“…Wright and Elias (1979) found significantly smaller response compatibility effects for old than for young subjects. However, Farkas and Hoyer (1980) found that old subjects' performance was more severely disrupted than young subjects' when they responded to a target in the presence of similarly shaped distractors (see also R. Shaw, 1991). Cerella (1985a) hypothesized that these discrepant findings might be the result of uncontrolled age-related acuity differences rather than attentional factors.…”
Section: Stopping Taskmentioning
confidence: 99%
“…It has frequently been reported that aging is accompanied by a loss in the ability to ignore distractor information (e.g., Farkas & Hoyer, 1980;Hoyer et al, 1979;Madden, 1992;Plude & Hoyer, 1986;Rabbitt, 1965;Wright & Elias, 1979). Although these findings can be accounted for in a variety of ways (for reviews, see Hartley, 1992;Madden & Plude, 160 L. Kotary and W .…”
Section: Lisa Kotary and William J Hoyermentioning
confidence: 99%
“…It should be noted that if the target location is constant there is little or no difference due to aging (Carlson, Hasher, Connelly, & Zacks, 1995;Farkaas & Hoyer, 1980). Older people appear to benefit more than younger people when presented with advance cues indicating the future location of a visual search target (Kline & Scialfa, 1996).…”
Section: Vision and Agingmentioning
confidence: 99%